Investigation of the immobilization of probiotics as a method for their protection and delivery to the human gastrointestinal tract - Gavrilova N.; Chernopolskaya N.; Bannikova A.; Evdokimov I.; Shramko M. (Техника и технология пищевых производств)
The relevance of research is the experimental and analytical justification of the effectiveness of the joint use of biopolymers of animal and plant origin as a substrate in the process of immobilization of the association of probiotic cultures. Researches are executed in specialized laboratories of universities: Omsk GAU, Saratov GAU, SKFU. In the form of a substrate were used: gelatin, χ-carrageenan, low-esterified pectin, modified starch; as bioobjects are selected: L. acidophilus, B. Lactis, S. thermophilus. To obtain reliable and complete characteristics, a set of research methods was used in the work: physicochemical, sensory, and microbiological. Investigation of immobilization allowed to determine the optimal ratio of biopolymers as a carrier (substrate): pectin and gelatin, as 2:1; the total concentration of solids of the carrier solution (20.0 ± 0.5)% by weight. The total number of viable cells of probiotic microorganisms in membranes (plates) is an average of lg (11.0 ± 0.55). In order to extend the shelf life, the membranes were dried in a freeze dryer, with parameters: the temperature of the frozen product (–25 °C) and the residual pressure in the sublimate 0.013–0.133 kPa. Immobilization by microencapsulation of the association of probiotic cultures of L. acidophilus, B. Lactis and S. thermophilus into a gel of biopolymers: gelatin food, pectin gene LM 106 AS-YA, starch in a ratio of 5:1:1 was studied by microencapsulation. The obtained microcapsules were studied in imitated gastric and intestinal conditions, while the number of viable probiotic cells was determined at different times of their degradation. It was established that 20–25% of viable cells of probiotics were released from capsules in the "artificial stomach" phase, 75–80% in the "artificial bowel" phase. Innovative biotechnologies of milk based products for specialized nutrition are presented.